Respuesta :

Answer:   w = 7,  x = 6

Step-by-step explanation:  Solve by substitution

W + b = 13

rewrite as   b = 13 - w  and substitute that value for b in the second equation

6.5w + 2b = 57.5  Then solve for w

6.5w + 2(13-w) = 57.5 . Distribute

6.5w + 26 - 2w = 57.5 .  Subtract 26 from both sides. Combine like terms and simplify

6.5w - 2w = 57.5 - 26

4.5w = 31.5  Divide both sides by 4.65

w = 7 . Substitute 7 for w in the first equation and solve for b

7 + b = 13 . Subtract 7 from both sides

b = 6

ACCESS MORE